CREATIVE CONSPIRACY : THE NEW RULES OF BREAKTHROUGH COLLABORATION - Thompson, Leigh L., author 401075 (Boston, Mass. : Harvard Business Review Press, 2013)
"Embracing the Counterintuitive Side of Collaboration... Think of your to-do list at work. Chances are the most important tasks require you to work with others--and the success of those endeavors depends on the effectiveness of your collaboration. According to management expert Leigh Thompson, collaboration that is conscious, planned, and focused on generating new ideas builds excitement and produces what she calls a "creative conspiracy." Teams that conspire to organize themselves, motivate one another, and combine their talents to meet creative challenges are the hallmark of the most successful organizations. In this book, Thompson reveals the keys to the kind of collaboration that allows teams to reach their full creative potential and maximize their results. She also reveals a host of surprising findings; for example: (1) Left to their own devices, teams are less creative than individuals, (2) Providing "rules" to teams actually increases inventiveness, (3) Striving for quality results in less creativity than striving for quantity, (4) Fluctuating membership enhances a team's innovation, and (5) Most leaders cannot articulate the four basic rules of brainstorming. Thompson combines broad-ranging research with real-life examples to offer strategies and practices designed to help teams and their leaders capitalize on what actually works when it comes to creative collaboration. "Creative Conspiracy" challenges managers to adopt an unconventional approach to leading teams that, done right, will lead to the creative success of every team--and every organization."--